An Analysis of the Impact of Promotion Strategies on Buying Decision and Buying Amount on Dunkin' Donuts Jambi - Wella Sandria; Theresia Dhian Kusumawati; Veni Reza; Astri Ayu Purwati (Yayasan Riset dan Pengembangan Intelektual, 2022)
This study aims to determine the characteristics of Dunkin' Donuts consumers in Jambi City and analyze the impact of promotional strategies on buying decisions and purchase quantities at Dunkin' Donuts Jambi City. This study uses primary data obtained from the results of questionnaire answers from respondents to find out the reasons for consumers to decide to buy at Dunkin' Donuts, Jambi City. The number of samples in this study were 95 respondents by using purposive sampling technique. Analysis of the data used is descriptive quantitative analysis to describe the characteristics of consumers and chi-square test to determine the impact of promotional strategies with buying decisions and the amount of promotion. Based on the results of the analysis, it was found that the characteristics of the majority of respondents based on gender were women, based on the age of 21-22 years, based on semester level was 6 and based on purchase intensity was 1 time in 1 month. The results of the chi-square test indicate that promotional media have a positive and significant impact on buying decisions (X2 count 3.470 > X2 table 2.7326) and promotional media have a positive and significant impact on the buying amount (X2 count 12.1992 > X2 table 5,2260). Keywords: Buying Amount, Buying Decision, Promotion Strategies